2008
DOI: 10.1128/jcm.00319-08
|View full text |Cite
|
Sign up to set email alerts
|

Proportions of Mycobacterium massiliense and Mycobacterium bolletii Strains among Korean Mycobacterium chelonae-Mycobacterium abscessus Group Isolates

Abstract: Korean isolates of the Mycobacterium chelonae-Mycobacterium abscessus group, which had been isolated from two different hospitals in South Korea, were identified by PCR restriction analysis (PRA) and comparative sequence analysis of 16S rRNA genes, rpoB, and hsp65 to evaluate the proportion of four closely related species (M. chelonae, M. abscessus, M. massiliense, and M. bolletii). Of the 144 rapidly growing mycobacterial strains tested, 127 strains (88.2%) belonged to the M. chelonae-M. abscessus group. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
111
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 40 publications
(51 reference statements)
10
111
4
1
Order By: Relevance
“…The rate of isolation of M. massiliense from infected patients in Korea is much higher than that in recent reports 6,9 . An epidemic occurred in Korea associated with intramuscular injection of antimicrobial agents, and the causative microorganism was finally identified as M. massiliense 8 .…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…The rate of isolation of M. massiliense from infected patients in Korea is much higher than that in recent reports 6,9 . An epidemic occurred in Korea associated with intramuscular injection of antimicrobial agents, and the causative microorganism was finally identified as M. massiliense 8 .…”
Section: Discussioncontrasting
confidence: 40%
“…abscessus 2,7,8 ; therefore, 16S rRNA gene sequencing cannot discriminate between these species. M. massiliense can be differentiated from M. abscessus by sequencing of the rpoB, hsp65, sodA, and recA genes, or the 16S-23S rRNA internal transcribed spacer sequence [6][7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of M. massiliense isolation appears to vary regionally (Harada et al, 2012;Kim et al, 2008;van Ingen et al, 2009;Zelazny et al, 2009). Recently, it was further reported that M. massiliense in Korean patients could be subdivided into two genotypes based on hsp65 sequence analysis (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%